Characterization of Copper Phthalocyanine-Tetrasulfonic Acid Tetrasodium Salt /Graphene Oxide - Kazem, Mayada Waheed; Jalal, Raed Kamel (Iraqi Journal of Science, 2021)
In this paper, the pure graphene oxide and copper phthalocyanine-tetrasolfonic acid tetrasodium salt were used to prepare thin films by using the spin coating method. These chemical compounds have remarkable optical properties and are chemically used in the development of device sensors by increasing the mixing ratio. Three different mixing ratios were prepared at room temperature and 150oC annealing temperature for three hours. The spectra of UV-VIS-IR absorption, photoluminescence, and Fourier-transformed infrared (FT-IR) were studied.